Transformação de conflitos e os movimentos pela paz na Colômbia: uma pesquisa comparada dos processos de paz durante os Governos Pastrana (1998-2002) e Santos (2010-2016) - Bezerra, Catarina Rose (2017)
This dissertation aims to identify the role of peace movements – and civil society – in transforming the 20th century conflict in Colombian. It presents a comparative analysis of the peace processes of the governments of Andrés Pastrana (1998-2002) and Juan Manuel Santos (2010-2014). This research starts from the assumption that such movements are essential in the construction of peace, especially in the Colombian context, in which the conflict originated from social dissatisfaction. For this, the critical approach of Peace Studies will be used, turning to the idea of transformation or transcendence of conflicts, diverging from traditional institutional models. This choice provides spaces to think beyond the formal peace process and the signing of a document or agreement. The work will be structured in four sections. In the first one, the theoretical basis to be used will be formulated, seeking also to build a bias of Peace Studies. The second chapter will then present the recent history of the conflict, focusing on the dialogues conducted before 1998 and in the peace movements. The third topic will present the peace processes implemented in the governments of Pastrana and Santos, in an in-depth study, seeking to identify failures, the corrective actions, and the participation or not of the civil society. In the end of same topic, it will be make a comparison between the two periods in question, based on the variables raised in the previous chapter. Lastly, the conclusions and perspectives on peace-building in the post-agreement scenario will be presented.